Correlation of Production (Mortality and Weight Gain) with Status and Level of Biosecurity Implemented on Layer and Broiler Farms in West Java, Bali and South Sulawesi - Sarini, Ni Putu; Karim, Hasmida; Patrick, Ian Walter (Acta VETERINARIA Indonesiana, 2013)
Biosecurity is the most effective way to prevent farms from Avian Influenza outbreak that affect most of broiler and layer farms. This paper discussed the status and level of biosecurity implemented by small and big farms (broiler and layer) in the three provinces. In addition to that is to determine if there is any correlation between mortality and weight gain to both status and level biosecurity implemented by farmers. Results showed that small layer and broiler farms have similar biosecurity status in Java and Bali but not in South Sulawesi. While small and big layer producers on both types of farms are also have similar biosecurity status in the three provinces. Regarding to the level of biosecurity implemented the three provinces has their own characteristic of implementation. Both status and level of biosecurity implemented do not have correlation on mortality in both types of farms neither on broiler weight gain.